Social Problems of Women with Breast Cancer - Afield Study in Nanakaly Hospital in Erbil city (Raparin Journal of Humanities (RJH), 2024)
This research was conducted under the title (Social Problems  of  Women with Breast Cancer - Afield Study in Nanakaly Hospital in Erbil city) done. the main aim of this Research is to become  familiar with Social Problems that Women  with Breast Cancer face. In this study, the  Quality Method and the semi- open  meeting tools is used to data Collect information. The research community Nanakaly hospital in Erbil. The Study sample is aimed at women with cancer, with (273) women in (2021) the study sample is (12) women. The results of the Study point out that, women with breast cancer have family problems. Also, in terms of social relations, Women Will have Problems and they connect mix with people and they are afraid that people will say bad things to them. Economically, the will have problems and will not be able to provide for them. Sexually, women do net have sexual desires when they are sick and use drugs, their hair is cut off, their eyebrows are moved, their skin color is damaged and they suffer a lot of physical pain when using chemical injections, chemical pills and radiation treatment.